The Christmas bouquet - Woods, Sherryl (Don Mills, Ontario : Harlequin MIRA, 2014)
"For the very driven medical student Caitlyn Winters, catching the bridal bouquet at a Christmas wedding has set off a chain reaction that she's sure is more curse than blessing. Not only has she fallen in love with family medicine resident Noah McIlroy, but an unexpected pregnancy threatens her well-laid plans for the future. It doesn't help that Noah--with a whole lot of help from her O'Brien relatives--is completely on board with the prospect of marriage and happily-ever-after. It takes a whole lot of patience, love and family persuasion to help Caitlyn realize that she can still have everything she ever wanted, including a home in her beloved Chesapeake Shores and a man who understands all of her dreams"-- Book jacket.
Keywords: Women medical students -- Fiction; Man-woman relationships -- Fiction; Christmas stories; Chesapeake Bay Region (Md. and Va.) -- Fiction; Love stories